2022
DOI: 10.3389/fenvs.2022.1006142
|View full text |Cite
|
Sign up to set email alerts
|

Mutual effects of CO2 emission reduction and air pollution control policies in beijing-tianjin-hebei region

Abstract: To meet the carbon neutrality target and Beautiful China goal, the co-control strategy of carbon emission and air pollution is crucial. The Beijing-Tianjin-Hebei region is a prominent cooperative development zone, which faces dual challenges of CO2 emission reduction and air pollution control. This study aims to find the co-benefit pathway for achieving both targets in Beijing-Tianjin-Hebei. Based on an innovative and integrated framework by linking the computable general equilibrium model, atmospheric environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The prolonged suspension of fine particles in the atmosphere facilitates the formation of PM 2.5 pollution. Research indicates that industrial emissions, along with coal and biomass combustion for daily living, are principal sources of PM 2.5 [14][15][16]. Additionally, socio-economic and meteorological factors, as well as the generation of secondary particulate matter, further contribute to PM 2.5 pollution [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The prolonged suspension of fine particles in the atmosphere facilitates the formation of PM 2.5 pollution. Research indicates that industrial emissions, along with coal and biomass combustion for daily living, are principal sources of PM 2.5 [14][15][16]. Additionally, socio-economic and meteorological factors, as well as the generation of secondary particulate matter, further contribute to PM 2.5 pollution [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, China is now faced with dual challenges, including air pollution control and carbon mitigation. The uniqueness of today's atmospheric environment urges the Chinese government to explore a well-developed policy or governance strategy with aim of achieving a "win-win" situation of air pollutants and CO2 emissions control (Wu et al, 2022). Identifying the mechanism behind various factors influencing the performance of synergistic governance is the key point to provide valuable suggestions for the further realization of carbon neutrality and air quality improvement in China.…”
Section: Introductionmentioning
confidence: 99%
“…According to the existing literature regarding the evaluation on the co-benefit and co-control performance between air pollution and carbon mitigation, the synergistic effect was analysed from the perspective of comprehensive consideration of the respective relationship between carbon dioxide and air pollutant emission, or building one indicator or parameter to represent the degree of co-benefit or co-control (Dong et al, 2019a;Wu et al, 2022;Yi et al, 2022). In this paper, an index system approach is performed to measure the synergy degree, defined as the coupling coordination degree between two subsystems.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, many studies have quantified the air quality co-benefits of climate policies [2,[16][17][18][19][20]. These studies have shown that these co-benefits can partially cover or even offset the cost of mitigation [2,18], while there is significant regional and sectoral heterogeneity [2,18].…”
Section: Introductionmentioning
confidence: 99%